Analisis Faktor-faktor yang Berpengaruh pada Minat Pemilihan Karir Akuntan Publik dan Akuntan Non Publik Mahasiswa Akuntansi - Triono, Hermawan; Minarso, Bambang (Jurnal Ilmiah Aset, 2018)
This study aims to examine factors that affect the interests of career selection between public accountants and non-public accountants in Dian Nuswantoro University and AKI University. The population used in this study was 70 accounting students. The sampling technique used was purposive sampling. And the data were analyzed using multiple linear regression analysis The results showed that financial reward, professional recognition, social values, work environment, and labor market considerations have a positive and significant effect to the career selection.